Study on the Physical Conditions of Horses for Better Management of Welfare in Conditions of Climate Change in the Diourbel Region, Senegal - Ousmane KANE; Alkaly BADJI; Abdoulaye FAYE; Mariama BADIANE (International Journal of Medical Science and Clinical Research Studies, 2025)
OBJECTIVES: This quasi-experimental study aimed to investigate the effects of the "Application ODS" mobile app on educating one-day surgery (ODS) patients about anesthesia practices, specifically its impact on their knowledge and clinical outcomes. METHODS: The sample consisted of 62 ODS patients at Lampang Hospital, randomly divided into experimental (n=31) and control (n=31) groups. The "Application ODS," a general information questionnaire, a knowledge assessment form, and a clinical outcome record form were utilized. Data analysis employed descriptive statistics, paired t-test, independent t-test, and chi-square test. RESULTS: Pre-test and post-test scores the experimental group's mean knowledge score increased significantly more (11.03±0.65 to 17.83±0.73) than the control group's (10.77±0.55 to 12.55±0.77) (p<0.001). The experimental group achieved a high knowledge level and had no adverse events, with significantly lower hospital stay rates than the control group (p=0.015, p=0.019). Surgery cancellation or postponement did not differ significantly between groups. CONCLUSIONS: The "Application ODS" effectively increased ODS patients' knowledge and improved some clinical outcomes. Widespread adoption should be promoted to enhance healthcare quality and safety for this patient group. Further app development based on user needs and larger, long-term studies are recommended to inform appropriate policies.